2014
DOI: 10.5812/hepatmon.23552
|View full text |Cite
|
Sign up to set email alerts
|

Association of Upregulated HMGB1 and c-IAP2 Proteins With Hepatocellular Carcinoma Development and Progression

Abstract: Background:Hepatocellular carcinoma (HCC) is one of the most important health problems in China.Objectives:This study analyzed expression of high-mobility group protein B1 (HMGB1) and inhibitor of apoptosis protein-2 (c-IAP2) proteins in HCC compared to paired para-tumor tissue samples to assess the association with HCC pathogenesis and progression.Materials and Methods:Sixty-eight HCC and para-tumor tissue samples were collected for Western blot, qRT-PCR and immunohistochemical analyses of HMGB1 and c-IAP2.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Wang et al, also has been summarized the HMGB1 signaling pathway in HCC development 33 . In addition, Bi et al, found that HMGB1 upregulated with HCC progression 34 . However, the correlation between HMGB1 polymorphisms and HCC progression is never discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, also has been summarized the HMGB1 signaling pathway in HCC development 33 . In addition, Bi et al, found that HMGB1 upregulated with HCC progression 34 . However, the correlation between HMGB1 polymorphisms and HCC progression is never discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Bi et al also found the expression of HMGB1 and c-IAP2 proteins in cancer to be significantly associated with each other. [18] HMGB1 expression had a positive correlation with c-IAP2 and pERK, suggesting that HMGB1 may affect the expression of c-IAP2 via the activity of pERK. Recent research has shown that HMGB1 binds to CXCR4, which activates multiple signaling pathways, including ERK.…”
Section: Discussionmentioning
confidence: 99%
“…For HCC, some cell cycle proteins and proliferation cytokines are central in the proliferation, such as cyclin D1 and proliferating cell nuclear antigen (PCNA). HMGB1 not only increased cyclin D1 and PCNA to induce the proliferation of HCC [ 47 ], but also regulates for tumor multiplicity and size, alpha-fetoprotein (AFP) level and advanced TNM stage in HCC [ 48 ], indicating HMGB1 could be used as a biomarker for HCC diagnosis which deserves further study [ 49 ].…”
Section: Hmgb1 and Cell Proliferation In Hccmentioning
confidence: 99%